THE INFLUENCE OF TEACHER'S GESTURES TO STRENGTHENING THE UNDERSTANDING OF MATHEMATICS STUDENTS - Syahrir, Nasrun Accung; As'Ari, Abdur Rahman (Universitas Negeri Malang, 2019)
This research examines about gestures that can be used in learning math in the classroom to strengthen the understanding of students of the material being taught teachers, in this article, I showed the evidence taken from the teacher and the student movement for proving that mathematics can be realized. This research is descriptive research with the kind of data analysis on the research of these video recordings of teachers who carry out learning and research subject processed there are 2 teachers from 5 teachers are observed. We present evidence for a student and a teacher produces gestures when they explain the concepts and ideas of mathematics. The results of this study suggested that gestures have the power so that children quickly understand and understand the learning delivered teacher, and any gestures each had a special movement such as; (a) strengthened understanding pointing gestures students through movement within the physical environment, (b) strengthen representational understanding gestures students through mental simulation, action and perception, and (c) empower students through writing movement action be evidence of permanent marks on a sheet of paper, a whiteboard or visual media. Thus, the teacher's gestures are very important because it can strengthen the understanding of students of material studied in class.